Analysis of the Accounting Treatment of Biological Assets on Agricultural Activities based on PSAK 69 (Case Study at PT. Galasari Gunung Sejahtera) - Farah Fauziah; Driana Leniwati; Riska Harventy (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the accounting treatment of biological assets on agricultural activities at PT. Galasari Gunung Sejahtera, whether it is in accordance with PSAK 69. To achieve the objectives of this study, the research was conducted at PT. Galasari Gunung Sejahtera. The method used is a qualitative descriptive approach. Qualitative data obtained through observation, interviews, and documentation. The analytical technique used in this research is data reduction, data presentation and conclusion drawing. The results of the study showed that PT. In general, Galasari Gunung Sejahtera has implemented PSAK 69, but in the reassessment section, PT. Galasari Gunung Sejahtera does not revaluate the value at the end of each period. This is because biological assets cannot be measured reliably. This is permitted, in accordance with paragraph 30 of PSAK 69.